Correction to: Toward a comprehensive view of cancer immune responsiveness: a synopsis from the SITC workshop. Issue 1 (4th July 2019) - Bedognetti, Davide; Ceccarelli, Michele; Galluzzi, Lorenzo; Lu, Rongze; Palucka, Karolina; Samayoa, Josue; Spranger, Stefani; Warren, Sarah; Wong, Kwok-Kin; Ziv, Elad; Chowell, Diego; Coussens, Lisa M.; et al.
Abstract : Following publication of the original article [1], the author reported that an author name, Roberta Zappasodi, was missed in the authorship list.